Charles Kingsley : the work and influence of Parson Lot. - Brown, Henry W. (London : Fisher, 1924)
Bibliotheeh E. Anseele
Dedicator: The British Co-operative Union, dedicatee: Anseele, Edward (sr.)
Met een opdracht aan E. Anseele
Engels
Monografie